Coordinate expression of the endogenous p53 gene in beta cells of transgenic mice expressing hybrid insulin-SV40 T antigen genes. - Efrat, S (1987)
The expression of p53 has been evaluated during oncogenesis of the pancreatic beta cells in transgenic mice harboring hybrid insulin-SV40 T antigen genes. Significant levels of p53 are detected in all cells expressing large T antigen. In contrast, the protein is undetectable in normal beta cells. There is a complete correspondence between the onset of expression of T antigen and the appearance of the endogenous p53 protein. In tumors, the two proteins are found in a complex. In addition, free uncomplexed T antigen is detected in every cell which expresses the transgene. These results are consistent with the participation of p53 in T antigen-induced tumorigenesis in vivo. The early appearance of p53 in all beta cells expressing large T cannot readily explain the progression of a small fraction of these cells into solid tumors.